The modification of surgical treatment in pelvic organ prolapse due to systematic surgical training – initial report - Klimczak, Krzysztof; Katulski, Jarosław; Malinowski, Andrzej; Dejewski, Cezary (Menopause Review/Przegląd Menopauzalny, 2007)
Objectives: Pelvic organ prolapse is one of the most common disorders reported to the gynaecologist. The standard operations for pelvic organ prolapse for years were the various types of colporrhaphy. The development of new surgical techniques (vaginal mesh implant) brought new concepts in vaginal correction of pelvic organ prolapse. Design: The purpose of this study was to present the results of modification of vaginal surgery in pelvic organ prolapse in a one-year intensive training period. Material and methods: 69 operations in pelvic organ prolapse were performed in the Gynaecological Ward of Tuchola District Hospital, from 02.06.2006 to 02.06.2007. DTOT procedure was performed in 31 patients (44.9%); in 18 cases SSLF was performed (26%). 9 patients (13%) were treated with conservative colporrhaphy. The reported period was compared to the period from 01.06.2005 to 01.06.2006, when 33 operations in pelvic organ prolapse were performed. DTOT represented 3%, SSLF 21% and conservative colporrhaphy 72.7% of all the patients. Results: A 42% increase in the number of DTOT procedures in the reported period was observed. The proportion of conservative colporrhaphies decreased from 72.7% to 13%. Inconsiderable increase in the number of SSLF procedures was observed (from 21% to 26%). This result was generated by modification of the route of hysterectomy that took place earlier – nowadays we perform 51% vaginal hysterectomy, 11.7% abdominal hysterectomy and 37.3% laparoscopic hysterectomy. Conclusions: It seems impossible to reach strong conclusions in terms of treatment effects because of the quite short period of observation of patients operated on in Tuchola Hospital. Nevertheless, prospective observation of the patients and absence of perioperative complications should confirm the priority of mesh implants application in treatment of pelvic organ prolapse. Further observations to determine concrete, prospective conclusions will be provided.